2019
DOI: 10.1038/s41598-019-45431-5
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Treatment in Chronic Kidney Disease: Multistage Pairwise and Network Meta-Analyses

Abstract: Pairwise and network meta-analyses on the relationship between the efficacy of the use of statins with or without ezetimibe and reductions in low-density lipoprotein cholesterol (LDLc) and C-reactive protein (CRP) in patients with chronic kidney disease (CKD) are presented. In the pairwise meta-analysis, statins with or without ezetimibe were shown to be efficacious in reducing major adverse cardiovascular events (MACE) in patients with CKD and an estimated glomerular filtration rate (eGFR) of less than 60 ml/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
(83 reference statements)
0
15
0
1
Order By: Relevance
“…Previous studies in paired and network meta-analyses on the relationship between the efficacy of statin use with or without ezetimibe and the reduction of low-density lipoprotein cholesterol (LDLc) and C-reactive protein (CRP) in patients with chronic kidney disease (CKD) are presented. Evaluation of the benefits of the drug can lead to individual therapy for CKD patients: Lowering cholesterol for CKD patients with high LDLc and CRP levels is recommended (15). Moreover, other previous study found that both hypercholesterolemia and low highdensity lipoprotein cholesterol (HDL-C) were independently associated with albuminuria (OR = 1.49, 95% CI 1.08 -2.07 and OR= 1.53, 95% CI 1.13 -2.09, respectively) (16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in paired and network meta-analyses on the relationship between the efficacy of statin use with or without ezetimibe and the reduction of low-density lipoprotein cholesterol (LDLc) and C-reactive protein (CRP) in patients with chronic kidney disease (CKD) are presented. Evaluation of the benefits of the drug can lead to individual therapy for CKD patients: Lowering cholesterol for CKD patients with high LDLc and CRP levels is recommended (15). Moreover, other previous study found that both hypercholesterolemia and low highdensity lipoprotein cholesterol (HDL-C) were independently associated with albuminuria (OR = 1.49, 95% CI 1.08 -2.07 and OR= 1.53, 95% CI 1.13 -2.09, respectively) (16).…”
Section: Discussionmentioning
confidence: 99%
“…After assessing study quality [20], and before applying planned contextualization techniques [21][22][23], pairwise and network meta-analyses of cardiac-and noncardiac-surgery-patient aggregate-level data were performed. The overall odds ratio (OR) and 95% confidence interval (CI) were obtained for various postoperative outcomes corresponding to the use of NIRS monitoring (POCD/POD, MACEs, AKI, bleeding/need for transfusion, and mortality) by the Mantel-Haenszel random-effects method.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional pairwise meta-analysis is insufficient when many options for tools (interventions) exist (e.g., when several drugs are available for the same treatment strategy). Network meta-analysis provides a viable solution, even though some interventions/exposures have never been compared head to head in RCTs [21]. Furthermore, to the best of our knowledge, this is the first contemporary review of NIRS monitoring in both types of major procedures.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Bayesian network analysis is an extension of traditional meta-analysis, which can make indirect comparisons of two treatments through a common comparator in the absence of head-to-head direct randomized controlled trials (Herrera-Gomez et al, 2019). Therefore, we performed a Bayesian network analysis to evaluate the relative proteinuria reduction and blood pressure changes by various ACEIs or ARBs or their combination for normotensive patients with CKD.…”
Section: Introductionmentioning
confidence: 99%